Marine Sponge-Derived Streptomyces sp. SBT343 Extract Inhibits Staphylococcal Biofilm Formation - Balasubramanian, Srikkanth; Othman, Eman M.; Kampik, Daniel; Stopper, Helga; Hentschel, Ute; Ziebuhr, Wilma; Oelschlaeger, Tobias A.; Abdelmohsen, Usama R. (Frontiers in Microbiology, 2017)
Staphylococcus epidermidis and Staphylococcus aureus are opportunistic pathogens that cause nosocomial and chronic biofilm-associated infections. Indwelling medical devices and contact lenses are ideal ecological niches for formation of staphylococcal biofilms. Bacteria within biofilms are known to display reduced susceptibilities to antimicrobials and are protected from the host immune system. High rates of acquired antibiotic resistances in staphylococci and other biofilm-forming bacteria further hamper treatment options and highlight the need for new anti-biofilm strategies. Here, we aimed to evaluate the potential of marine sponge-derived actinomycetes in inhibiting biofilm formation of several strains of S. epidermidis, S. aureus and Pseudomonas aeruginosa. Results from in vitro biofilm-formation assays, as well as scanning electron and confocal microscopy, revealed that an organic extract derived from the marine sponge-associated bacterium Streptomyces sp. SBT343 significantly inhibited staphylococcal biofilm formation on polystyrene, glass and contact lens surfaces, without affecting bacterial growth. The extract also displayed similar antagonistic effects towards the biofilm formation of other S. epidermidis and S. aureus strains tested but had no inhibitory effects towards Pseudomonas biofilms. Interestingly the extract, at lower effective concentrations, did not exhibit cytotoxic effects on mouse fibroblast, macrophage and human corneal epithelial cell lines. Chemical analysis by High Resolution Fourier Transform Mass Spectrometry (HRMS) of the Streptomyces sp. SBT343 extract proportion revealed its chemical richness and complexity. Preliminary physico-chemical characterization of the extract highlighted the heat-stable and non-proteinaceous nature of the active component(s). The combined data suggest that the Streptomyces sp. SBT343 extract selectively inhibits staphylococcal biofilm formation without interfering with bacterial cell viability. Due to absence of cell toxicity, the extract might represent a good starting material to develop a future remedy to block staphylococcal biofilm formation on contact lenses and thereby to prevent intractable contact lens-mediated ocular infections.